Analysis of the Italian honey market - O. O. Medvid; Zh. O. Peredera; N. S. Shcherbakova; S. B. Peredera (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
In the areas of the European Union, which are traditionally considered honey producers, we are observing a decrease in nectar resources and a decrease in the number of bee colonies due to anthropogenic factors, the destructive influence of pesticides and other chemical compounds, the development of new parasitocenoses, climate changes and experimental phenomena accompanying these changes, according to FAO, the population bees decreased by 37 %. Due to climate changes, honey production is decreasing in Italy. Honey consumption in the European Union exceeds production with self-sufficiency by 60 %. In 2021, the leading honey suppliers were Ukraine (which supplies 30 % of EU imports) and China (almost 28 % of EU imports). Comparing the data with 2020, we can note the increase in imports from China by 30 %). Since 2015, the European Commission has been monitoring the European honey market, noting a significant percentage of fraud and falsification of honey sold in the EU. Among the imported batches of honey in the EU in 2021 and 2022, almost every second (46 %) is suspected of adulteration, according to the results of “From the Hives” Joint Research Center (JRC) of the European Commission. Honey for sale must comply with Directive UE 2001/110/CE. In the coordinated joint actions of the EU, called “Dagli alveari” by 15 EU member states, Switzerland, and the Netherlands, 320 samples of honey originating from 20 exporting countries were selected. The research aimed to establish the presence of sugar syrups of exogenous origin to increase the volume to obtain more profit. Out of 320 examined samples, 147 (46 %) turned out to be falsified; their indicators did not meet the Directive UE 2001/110/CE, and accordingly, they are not “natural honey”. Falsified batches of honey were imported from Ukraine and China (66 out of 89 is 74 %), and honey originating from Turkey (14 out of 15 is 93 %). Honey imported from Great Britain has the highest adulteration rate (10 out of 10, 100 %). In Italy, a comprehensive action plan has been introduced to prevent the falsification of honey. The new control plan should include a quantitative increase in samples for research and the use of more effective tests to detect falsification: nuclear magnetic resonance (RMN) and high-performance liquid chromatography (HPLC). Honey produced in Italy must have the inscription “Italian honey” on the label, while honey originating from the countries of the European Union must contain the inscription “mixture of honey originating from the EU countries”, indicating the names of the producing countries. If honey comes from non-EU countries, it should be written “a mixture of honeys from non-EU countries” with the name of the producer country added.